IMPLEMENTASI KRAN AIR DAN SABUN CUCI TANGAN OTOMATIS MENGGUNAKAN SENSOR INFRARED DI KANTOR PEMERINTAHAN - I Kadek Juliarta; Fajri Pratama; Putu Andi Aditya; I Nyoman Buda Hartawan; Ni Wayan Suardiati Putri Putri; Kadek Suryati; Evi Dwi Krisna; Ketut Sepdyana Kartini; I Wayan Gede Wardika; Wayan Eka Wijayanti (Yayasan Lavandaia Dharma Bali, 2022)
The COVID-19 pandemic has made people adopt a new lifestyle or can be called a new normal, this change covers all sectors of life from health, economy, to social, so that people inevitably have to adapt to new patterns of life. One of the policies of the Indonesian government to prevent transmission of the virus is to implement health protocols, including regular hand washing. The Government Office also provides water faucets for washing hands, but the water faucets are still conventional where you need to turn them first, therefore the author took the initiative to make water faucets and automatic hand washing soap using infrared sensors. The design of the tool uses a DC water pump, relay, and infrared sensor as the main component of the water faucet. The design process is divided into two phases, namely assembling the frame or place of the water faucet and assembling the electrical components. After the tool is complete, the results obtained are that the water faucet turns on when there is an object blocking the sensor and will stop 4 seconds after the sensor does not read the object, for hand soap it will turn on when the sensor is blocked and immediately turn off after the sensor does not read the object.